Persistent reduction of segment growth and photosynthesis in a widespread and important sub‐Arctic moss species after cessation of three years of experimental winter warming. (18th July 2016) - Bjerke, Jarle W.; Bokhorst, Stef; Callaghan, Terry V.; Phoenix, Gareth K.
Summary: Winter is a period of dormancy for plants of cold environments. However, winter climate is changing, leading to an increasing frequency of stochastic warm periods (winter warming events) and concomitant reductions in snow cover. These conditions can break dormancy for some plants and expose them to freeze‐and‐thaw stress. Mosses are a major component of high‐latitude ecosystems, yet the longer‐term impacts of such winter warming events on mosses remain unknown. In order to determine the longer‐term legacy effects of winter warming events on mosses, we undertook a simulation of these events over three consecutive winters in a sub‐Arctic dwarf shrub‐dominated open woodland. The mat‐forming feather moss, Hylocomium splendens (the most abundant cryptogam in this system), is one of the most widespread Arctic and boreal mosses and plays a key functional role in ecosystems. We studied the ecophysiological performance of this moss during the summers of the experimental period (2007–2009) and in the following years (2010–2013). We show that the previously reported warming‐induced reduction in segment growth and photosynthesis during the experimental years was persistent. Four years after the last event, photosynthesis and segment growth were still 30 and 36% lower than control levels, which was only a slight improvement from 44 and 43% 4 years earlier. Winter warming did not affect segment symmetry. During the years after the last simulated event, in both warmed and control plots, chlorophyll fluorescence and segment growth, but not net photosynthesis, increased slightly. The increases were probably driven by increased summer rainfall over the study years, highlighting the sensitivity of this moss to rainfall change. Overall, the legacy effects shown here demonstrate that this widespread and important moss is likely to be significantly disadvantaged in a future sub‐Arctic climate where frequent winter warming events may become the norm. Given the key importance of mosses for soil insulation, shelter and carbon sequestration in high‐latitude regions, such persistent impacts may ultimately affect important ecosystem functions. A Lay Summary is available for this article. Abstract : Lay Summary